Situational Factors and the Victim-Offender Overlap, Pennsylvania, 2013-2014 - Berg, Mark T. ([Verlag nicht ermittelbar], 2021)
This study examines explanations for the victim-offender overlap using data obtained from male prison inmates and a community sample. It employs two different designs, both of which are based on situational analyses of incidents. First, respondents are asked about their frequency of victimization and offending, as well as other behaviors. Second, respondents are asked about a violent and non-violent conflict in which they were recently involved.